Hydrodynamic pattern of high-speed droplet train impingement - Junaidy Lukman (2015)
Droplet train impingement is a series of droplets with constant droplet diameter, droplet velocity and droplet spacing. The general application of a droplet train impingement is for spray cooling, fuel injection in engine, spray paint, etc. A study of droplet train impingement on a superheated surface with different droplet velocity and impact angle is presented. A droplet generator with a piezoelectric oscillator was used to produce the droplet train. The designed droplet generator system was able to adjust parameters such as frequency of the droplet train, the diameter of the droplet produced, and the water pressure. A function generator was used to adjust he frequency of the droplet train. Droplet diameter was adjusted by changing the pinhole. Following the droplet generator system, a superheated surface was created using copper rod as the impingement surface and four heater cartridges as heating element to study the hydrodynamic pattern of the droplet impingement. Hydrodynamic pattern of the droplet impingement were captured using a high-speed camera. The effects of the water pressure on the spacing of the droplet, the velocity of the droplet and the diameter of the droplet were discussed. The velocity of the droplet was found to be 8.831 m⁄s at 10 psi, 11.430 m⁄s at 15 psi, 13.596 m⁄s at 20 psi, 15.367 m⁄s at 25 psi, 16.809 m⁄s at 30 psi, and 18.933 m⁄s at 35 psi. It was found that the increase in pressure would increase the spacing of the droplet, the velocity of the droplet and the diameter of the droplet. The diameter of the wetted area and the rebound angle of evaporated liquid were measured and discussed. The conclusions of the results were that droplet velocity had no or small effects to the wetted area and rebound angle. However, the impact angle had significant effects to the resulting rebound angle. The increase in impact angle would decrease the rebound angle before the rebound angle reach a certain constant value. In conclusion, the study of the effects of water pressure has been presented. The hydrodynamic pattern of droplet impingement has also been presented. In the future, a study of the heat performance as the results of variation of droplet velocity and variation of impact angle should be conducted.